2012
DOI: 10.1177/0899764011434554
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Generalized Trust on Volunteering in Japan

Abstract: There is limited understanding of how attitudinal variables such as generalized trust influence formal volunteering compared with demographic and socioeconomic variables. Using data from the 2005 Japanese General Social Survey (JGSS), this study examines the effects of generalized trust on regular and irregular formal volunteering in Japan. As the majority of studies on formal volunteering are based in Western countries, focusing on a non-Western society extends our knowledge of volunteering decisions. Japan i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…However, according to Taniguchi and Marshall (2014), the effect of trust may also highly depend on specific social contexts. In some countries, trust is unrelated or weakly related to citizen participation (Delhey and Newton 2003;Taniguchi 2013).…”
Section: Accountability and Transparency In Ngomentioning
confidence: 99%
“…However, according to Taniguchi and Marshall (2014), the effect of trust may also highly depend on specific social contexts. In some countries, trust is unrelated or weakly related to citizen participation (Delhey and Newton 2003;Taniguchi 2013).…”
Section: Accountability and Transparency In Ngomentioning
confidence: 99%
“…Taniguchi (2013) studies the relationship between generalized trust and volunteering, but Bowman (2004) focused specifically on the relationship between charitable confidence and volunteering, using data from the 2006 Giving and Volunteering study. In that application, charitable confidence is a single measure constructed from the average confidence that respondents have in 13 specific subsectors, including health organizations, religious organizations, and human services.…”
Section: Charitable Confidencementioning
confidence: 99%
“…Previous studies have shown that individuals’ volunteering and giving behaviors are influenced by their demographic characteristics and the stock of human, financial, cultural, and social capital that they possess (e.g., Bekkers, 2003, 2004; Jackson, Bachmeier, Wood, & Craft, 1995; Schervish & Havens, 1997; Smith, Kehoe, & Cremer, 1995; Taniguchi, 2012, 2013; Wilson & Musick, 1997). In these studies, human capital was consistently measured by education and health, and financial capital was measured by level of income.…”
Section: Literature Reviewmentioning
confidence: 99%